Jim Allison [videorecording (DVD)] : breakthrough - Haney, William M; Haney, William M; Harrelson, Woody; Allison, James P; Belvin, Sharon (Giant Interactive, 2019)
Looks at the career of Jim Allison who won the 2018 Nobel Prize for discovering the immune system's role in defeating cancer.